A comparative investigation on thermal, structural and optical properties of W and Nb-doped VO2-based thermochromic thin - Ersundu, A. E.; Ersundu, M. Celikbilek; Dogan, E.; Guven, M. B. (ELSEVIER SCIENCE SA, 2020)
In the present study, a simple sol-gel method was applied using different precursors to comparatively investigate thermal, structural and optical properties of W and Nb-doped VO2-based thin films using differential scanning calorimetry, X-ray diffraction (XRD), scanning electron microscopy and temperature-controlled ultraviolet-visible-near infrared spectroscopy techniques. For this purpose, vanadium precursors with different valence states were selected as starting materials and WCl6 and NbCl5 was used for W and Nb-doping, respectively to investigate the effect of dopant elements on thermochromic behavior. Therefore, soda-lime glass substrates were primarily coated with a SiO2 interlayer and subsequently VO2-based sols having different amounts of tungsten and niobium ions (0, 1, 2.5 and 5 mol%) were deposited by dip-coating method and annealed under different atmospheres. Thin films obtained using 4+ valence vanadium oxyacetylacetone showed poor surface adhesion properties, while 5+ valence vanadyl triisopropoxide based thin films exhibited excellent surface quality. A significant transmittance change with increasing temperature as an indication of the thermochromic property was observed for all samples. Structural analysis revealed that both dopant elements within the studied range formed solid solution with VO2, which was the only compound observed by XRD together with NaV6O15 phase due to the Na+ diffusion from the glass substrate. Both W and Nb doping simultaneously, increased luminous transmittance, modified solar energy modulation and decreased thermochromic transition temperature of VO2-based thin films. Thermochromic transition temperature was decreased from 65 to 41 degrees C and 26 degrees C with increasing Nb and W dopant content, respectively. Based on the results obtained in this study, it was determined that both W and Nb doping show great potentiality for the use of VO2-based thin films towards applications in energy-saving smart windows.
Keywords: Thermochromic; Thin film; Sol-gel; Vanadium oxyacetylacetone; Vanadyl triisopropoxide; Tungsten; Niobium; ENHANCED LUMINOUS TRANSMITTANCE; VANADIUM DIOXIDE; PHASE-TRANSITION; VO2 FILMS; INSULATOR-TRANSITION; VAPOR-DEPOSITION; SMART WINDOWS; COATINGS; MO; Materials Science; Physics